2010
DOI: 10.1590/s1679-45082010rw1517
|View full text |Cite
|
Sign up to set email alerts
|

Patients' anxiety before cardiac catheterization

Abstract: The nurses are responsible to provide a humanized assistance to offer a fast recuperation, minimize traumas of the hospitalization and the procedure. The knowledge of the causes and the strategies are fundamental to reduce the level of anxiety in pre-catheterization cardiac.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
15
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 14 publications
1
15
0
3
Order By: Relevance
“…A common diagnostic procedure undertaken in cardiology wards across the world is that of coronary angiography (CA) (King, Philpott, & Leary, ). Waiting for this invasive procedure can be a potential source of stress and anxiety for patients (Buzatto & Zanei, ). Anxiety causes haemodynamic stress responses that lead to increased myocardial oxygen consumption and the potential for harmful effects on cardiac functioning (Tahmasbi et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…A common diagnostic procedure undertaken in cardiology wards across the world is that of coronary angiography (CA) (King, Philpott, & Leary, ). Waiting for this invasive procedure can be a potential source of stress and anxiety for patients (Buzatto & Zanei, ). Anxiety causes haemodynamic stress responses that lead to increased myocardial oxygen consumption and the potential for harmful effects on cardiac functioning (Tahmasbi et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…2 Previous research has shown that patients undergoing clinical or surgical procedures such as coronary angiography often experience high levels of anxiety. 3,4 As such, methods to improve clinical outcomes and identify appropriate interventions to reduce patient anxiety are necessary.…”
mentioning
confidence: 99%
“…[4][5][6][7] Several studies have confirmed the effectiveness of providing information about the angiography process in reducing patient anxiety. 8,9 However, further research is required to identify the most effective approach and time to prepare a patient and their family for the procedure.…”
mentioning
confidence: 99%
“…A lack of knowledge about the PCI is documented as a cause of increasing anxiety pre‐procedure (Buzatto & Zanei, ; Mosleh et al, ). Therefore, educating patients before the PCI procedure might be promising for their anxiety levels (Chair et al, ).…”
Section: Introductionmentioning
confidence: 99%